EXPLORING TEACHER'S SCAFFOLDING TO THE STUDENTS IN TEACHING WRITING : A case study in one Junior High School in Parongpong - Kamil, Rohmat (2017)
The research entitled "Exploring Teacher's Scaffolding to Students in Teaching Writing" is focused at investigating teacher's ways to provide Scaffolding and challenges of implementing Scaffolding in teaching writing Descriptive text to seventh grade students in Parongpong, West Java, Indonesia. The data were collected from classroom observation, field notes, and semi-structured interview. The data obtained were transcribed and analyzed by using curriculum cycles framework (Hammond, 2001; Gibbons, 2002; Emilia, 2010). Besides, the data were also examined based on Scaffolding type theories (Roehler & Cantlon, 1997; Hammond, 2001; Gibbons, 2002; Walqui, 2006). The results revealed that six types of Scaffolding were used by the teacher in teaching writing. The most intensive Scaffolding was given in Building the Field and Modeling stage of the curriculum cycle, and all Scaffolding was reduced in the Independent Writing stage. The results also showed various ways were used by teacher to provide Scaffolding; asking previous lesson, providing illustration, explaning Grammar and text structure, giving students chance to participate in learning process, reading text model, and providing supportive and corrective feedback towards students' responses. Furthermore, some challenges faced by teacher in using Scaffolding were the amount of students, language intruction and time constraint. ;--- Penelitian yang berjudul " Ekplorasi Scaffolding yang diterapkan guru terhadap siswa pada pengajaran menulis" berfokus pada investigasi cara guru menyediakan Scaffolding dan tantangan dalam mengimplementasikan Scaffolding pada pengajarsan menulis teks Deskriptif kepada siswa kelas & di Parongpong, Jawa Barat, Indonesia. Data-data dikumpulkan dari observasi kelas, catatan lapangan, dan wawancara semi-terstruktur. Data-data yang diperoleh kemudian di transkrip dan di analisis dengan menggunakan kerangka kerja Curriculum cycle (Hammond, 2001; Gibbons, 2002; Emilia, 2010). Selain itu, data-data juga di uji berdasarkan teori tipe-tipe Scaffolding (Roehler & Cantlon, 1997; Hammond, 2001; Gibbons, 2002; Walqui, 2006). Hasilnya menunjukkan bahwa enam tipe Scaffolding telah digunakan oleh guru pada pengajaran menulis. Penggunaan Scaffolding paling intesif diberikan pada tahap Building the Field dan Modeling dalam curriculum cycle, dan semua scaffolding dikurangi pada tahap Independent Writing. selain itu, hasil studi menunjukkan bahwa guru menggunakan cara yang berbeda-beda untuk menyediakan Scaffolding, sperti; bertanya pelajaran sebelumnya, memberikan ilustrasi, menjelaskan tata bahasa (Grammar) da sturktur teks, memberi ksempatan siswa untuk berpartisipasi dalam proses pembelajaran, membaca teks model, dan memberikan umpan balik baik yang bersifat suportif maupun korektif terhadap respon siswa. Lebih lanjut, beberapa tantangan yang dihadapi guru saat menggunakan Scaffolding adalah jumlah siswa, bahasa intruksi dan keterbatasan waktu.